Le guide touristique: lieu de rencontre entre lexique et images du patrimoine culturel. Vol. II - Raus, Rachele; CAPPELLI, GLORIA; Flinz, Carolina (Strumenti per la didattica e la ricerca, 2017)
This book is the second part of the work devoted to the tourist guide as a meeting place between lexicon and images of cultural heritage, a work resulting from the colloquium which took place on June 11 and 12, 2015 in Pisa and Florence. This volume focuses on the image, as a representation of reality but also as a place from which the imagination can be exercised by evoking mental representations (the imaginary). The three proposed sections (I. Les images du voyage; II. L'art dans le guide; III. Les guides entre imaginaire et propagande) intend to suggest routes of reflection around the tourist guide, an object that has never ceased to transform and which, through the lexicon and images, has been able to transmit the most different and picturesque cultural heritages.